Characteristics of Mycoplasma hyopneumoniae Strain ES-2 Isolated From Chinese Native Black Pig Lungs - Zong, Bingbing; Zhu, Yongwei; Liu, Manli; Wang, Xiangru; Chen, Huanchun; Zhang, Yanyan; Tan, Chen (Frontiers in Veterinary Science, 2022)
Mycoplasma hyopneumoniae is the primary pathogen of swine enzootic pneumonia and causes great economic losses to the swine industry worldwide. In China, M. hyopneumoniae seriously hinders the healthy development of the native black pigs. To prevent and treat porcine respiratory disease caused by M. hyopneumoniae, the characteristics of M. hyopneumoniae strain ES-2 isolated from Chinese native black pig lungs with gross lesions at post-mortem were studied for the first time in this study. Strain ES-2 cell was round or oval cells and most sensitive to kanamycin. The diameters of most strain ES-2 cells ranged from 0.4 to 1.0 μm with maximum viability of 1010 CCU/ml. Experimental challenge of animals with strain ES-2 showed respiratory disease could be reproduced, with pneumonic lung lesions evident. Comparative genomics analysis identified that 2 genes are specific to pathogenic M. hyopneumoniae strains, which may be predicted to be a molecular marker. These findings suggest that the study on the characteristics of M. hyopneumoniae strain ES-2 will guide the rapid and accurate drug use in the clinic, and develop a theoretical foundation for accurately diagnosing and treating the infection caused by pathogenic M. hyopneumoniae.